Heavy metal accumulation, risk assessment and integrated biomarker responses of local vegetables: A case study along the Le'an river. (May 2018) - Ji, Yong; Wu, Peijun; Zhang, Jie; Zhang, Jun; Zhou, Youfeng; Peng, Yongwen; Zhang, Shifeng; Cai, Gaotang; Gao, Guiqing
Abstract: In this research, Ganzhou Chinese Cabbage ( Brassica rapa pekinensis ), Native Purple Garlic ( Allium sativum L) and Leping Radish ( Raphanus sativus L) widely planted and distributed along the Le'an River were chosen in the present study. Soil physical-chemical properties, nutrients contents as well as heavy metals elements accumulated in both soils and vegetables collected from 24 sites were analyzed by lab analysis combined with statistical method which was also used for calculation of contamination factor, pollution indexes and hazardous index. Heavy metals accumulation in soils were revealed with higher level, and copper and cadmium exceeded the background values by 8.82 and 16.73 times on average, which were also significantly related with the distribution of nonferrous metal processing enterprises. Heavy metal elements accumulated in vegetables were fully consistent with the finding of pollution characteristics in soils. Peroxidase biomarkers in vegetables, including superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), reduced glutathione (GSH) and lipoperoxidation (as TBARS), as well as integrated biomarker responses (IBR) were determined to give a reliable response after exposing of contaminants. Heavy metals accumulation ability and biomarker responses for three vegetables were usually determined in the following decrease trend: Ganzhou Chinese Cabbage > Native Purple Garlic > Leping Radish. Compared with peroxidase biomarkers activities or contents of control site, all the measured biomarkers in polluted sites showed significantly responses, indicating potential relationship between pollutants stresses and biomarker responses. This study also revealed that the IBR values were coordinated well with the pollutants concentrations. Graphical abstract: Image 1 Highlights: Tillage could improve soil structure and storage capacity for nutrients. Soils and vegetables showed significant differences in the enrichment ability of heavy metals. Vegetables were observed with multiple biomarker response patterns. IBR indexes presented with visualization coordinated well with heavy metals distribution.